Commitment or Control? HRM Practices in Female and Male-led Small Businesses - Verheul, Ingrid (Senate Hall, 2018)
Employee relations in small and medium-sized enterprises (SMEs) are often determined by the owner-manager who is faced with a trade-off between maintaining control and creating a positive and stimulating work environment to enhance employee commitment. This study investigates this trade-off in companies managed by female and male entrepreneurs. To test for gender differences use is made of a sample of 555 SMEs (with less than 100 employees) in the Netherlands. Contrary to what is generally believed, it is found that employee relations in female-led firms are more control-oriented than those in male-led firms. More specifically, female-led firms are more likely to be characterized by centralized decision-making and direct supervision of the production process. Keywords: gender, entrepreneurship, human resource management, commitment, control
Keywords: gender|entrepreneurship|human resource management|commitment|control